Mediação e conciliação como políticas públicas de acesso à justiça na comarca de Santana – AP - Silva, Davi Pinho da (2023)
For many years, almost all conflicts between society were submitted to the Judiciary as a way of solving them. This generated an excess of judicial demands, leading to a slow response to cases and making access to justice difficult. In an attempt to solve this problem, some legislation was created in order to implement Public Policies that would meet conflicting demands without the need for direct intervention by the Judiciary, facilitating access to justice and reducing the filing of lawsuits. Among these policies, mediation and conciliation stand out as self-resolving methods of Conflict Resolution, being implemented in the national territory through the creation of Judicial Centers for Conflict Resolution and Citizenship – CEJUSC. In this sense, it is necessary to investigate how mediation and conciliation contribute, as Public Policies, to access to justice and the reduction of the filing of lawsuits within the scope of the Judiciary in the municipality of Santana-AP. The present work is divided into a theoretical approach, where a study is made on the main self-composition methods (negotiation, arbitration, conciliation and mediation) and the impacts, in the lives of those under jurisdiction, of the implantation of mediation and conciliation in the Brazilian legal system. The methodological tool used was the qualitative and quantitative applied research, making use of the survey and data analysis, application of a questionnaire to professionals who work at CEJUSC in the Comarca de Santana and to the jurisdictional members served by this center and bibliographical consultation, where we sought to investigate the impact of these Public Policies on the life of the citizens of Santa Catarina. The results showed that the use of mediation and conciliation methods not only facilitate people's access to jurisdictional services, but also significantly contribute to the dejudicialization of demands and, consequently, to the unobstructing of the Judiciary.